Risk Factors for Early and Late Onset Preeclampsia in Reunion Island: Multivariate Analysis of Singleton and Twin Pregnancies. A 20-Year Population-Based Cohort of 2120 Preeclampsia Cases - Pierre-Yves Robillard; Malik Boukerrou; Gustaaf Dekker; Marco Scioscia; Francesco Bonsante; Brahim Boumahni; Silvia Iacobelli (Reproductive Medicine, 2021)
Objectives: To develop a multivariate model for risk factors specific to early onset preeclampsia (EOP) and late onset preeclampsia (LOP) in our entire population (singleton and twin pregnancies). Material and methods: 20 year-observational population-based historical cohort study (2001–2020). All consecutive births delivered at the Centre Hospitalier Universitaire Hospitalier Sud Reunion’s maternity ward. A standardized validated epidemiological perinatal database was used. Results: During the 20-year period, there were 81,834 pregnancies and 83,497 infants born, 1232 dichorionic and 350 monochorionic twin pregnancies. There were 2120 cases of preeclampsia, of which 2001 were preeclamptic singleton pregnancies and 119 twin pregnancies (incidence 7.5% in twin pregnancies vs. 2.5% singletons, OR 3.0, p < 0.001). Independent risk factors for EOP and LOP in a multivariate model (controlling for the two major confounders: maternal ages—both risks for EOP and LOP, and maternal pre-pregnancy BMI—specific risk factor for LOP) were: history of preeclampsia (adjusted OR (aOR) 11.7 for EOP, 7.8 for LOP, p < 0.0001), chronic hypertension (aOR 7.3 for EOP, 3.9 for LOP, p < 0.0001), history of perinatal death (aOR 2.2 for EOP, p < 0.0001 and 1.48 for LOP, p = 0.007), primipaternity (aOR 3.0 for EOP and 3.6 for LOP, p = 0.001), dizygotic twin pregnancies (aOR 3.7 for EOP, p < 0.0001 and 2.1 for LOP, p = 0.003), monozygotic twin pregnancies (aOR 3.98 for EOP, p = 0.003 and non-significant (NS) for LOP), ovulation induction (aOR 5.6 for EOP, p = 0.004 and NS for LOP), and in vitro fertilization (aOR 2.8 for EOP, p = 0.05 and NS for LOP). Specific to LOP and NS for EOP: renal diseases (aOR for LOP 2.9, p = 0.007) and gestational diabetes mellitus (aOR 1.2, p = 0.04). Conclusions: Maternal ages over 35 years, chronic hypertension, history of preeclampsia, ovulation induction, in vitro fertilizations, history of perinatal deaths and twin pregnancy (in our experience, especially mono zygotic twin pregnancies) are significant risk factors for EOP. New paternity is an independent factor for both EOP and LOP.